Analysis of the Static Protein Profile of Degenerated IVD Indicate Increased Fibrosis-Related Proteins. (May 2014) - Yee, A.; Tam, V.; Cheah, K.; Cheung, K. M. C.; Chan, D.
Introduction: Intervertebral disc (IVD) degeneration is a common world-wide occurrence and is classically associated with cellular, water and proteoglycan (PG) loss from the nucleus pulposus (NP) which can greatly affect IVD function. While several studies have demonstrated molecular changes during aging and degeneration, our understanding of the processes that occur during these events are limited. The identification and analysis of proteins that are present in the IVD during aging and degeneration may provide clues on the processes that occur during these two events, which was the aim of the present study. Materials and Methods: Ethics was approved by the IRB board, and both degenerated and non-degenerated IVD specimens (seven samples of each) were acquired with patient consent. The NP and AF were dissected from the IVD, and proteins underwent extraction with 4M GuHCl buffer, fractionation using CsCl density gradient ultracentrifugation, and then subsequently separated into insoluble/soluble protein fractions. The proteins then underwent trypsin digestion and iTRAQ labeling for quantitative analysis using LCMS/MS. Data were analyzed using ProteinPilot 4.0 Results: The proteins were first grouped into clusters to depict whether or not they were associated with increases, decreases or no change with increasing age. With increasing age, the AF of non-degenerated IVD had decreasing levels of collagen type I (soluble fraction) and types II and XI (soluble/insoluble fractions) which could impact on the tensile strength of the AF. A decreasing trend was also observed in the NP for collagen type II, however an increase in collagen type I was observed in the younger controls. In both AF and NP, increasing levels of decorin, lumican and PRELP were observed with increasing age, in addition to mimecan and biglycan in the NP. The identified proteins from the degenerated IVD was also clustered into increasing, decreasing, or no change in trend, and compared with the non-degenerated samples (controls) which indicated similar trends for both groups. Notable changes in the NP associated with degenerated samples included an accumulation of fibronectin and type I collagen (insoluble fraction) in younger degenerated samples, in addition to CILP and CILP2. In degenerated AF, there were increased levels of fibronectin, COMP and CILP, while aged and degenerated AP had increased aggrecan, decorin and PRELP (insoluble fraction). Conclusion: The data in this study indicate that degeneration and aging share both similarities and differences in the static protein profile. Alterations in the matrix and shifts in protein content are likely impinge on cell-matrix interactions in addition to matrix turnover, and aging and degeneration both exhibit fibrotic-related proteins. Of particular interest is the accumulation of collagen type I and fibronectin (also associated with fibrosis) in young and degenerated IVD from the insoluble fraction, an indication of increased cross-linked molecules that have accumulated over time. Such differences may be an important indicator of degeneration-associated changes and warrants further investigation. Studying the dynamic protein profile using SILAC technology and ex vivo culture of IVD samples will identify actively synthesized proteins in the IVD. This will provide valuable information on cellular functions in the IVD during aging and degeneration, which will be the focus of future studies. Disclosure of Interest None declared